An investigation into the use of radiographer abnormality detection systems by Queensland public hospitals. Issue 2 (29th April 2018) - Murphy, Andrew; Neep, Michael
Abstract: Introduction: A Radiographer Abnormality Detection System (RADS), such as the 'red dot system', involves radiographers highlighting the presence of potential acute abnormalities on radiographs in the emergency setting. The literature suggests little additional training is required of radiographers to participate in such a system, posing little impact on current workflow while remaining a cost‐effective, easy‐to‐implement program. However, its use outside the United Kingdom is sporadic. The purpose of this study was to investigate the frequency of use of a RADS in Queensland public hospitals. Methods: A cross‐sectional web‐based questionnaire was developed and distributed to 28 medical imaging department directors throughout metropolitan, rural and remote Queensland (Australia) public hospitals. The results of this survey were analysed using conventional descriptive statistics of response frequencies and the percentage of the sample. Results: The questionnaire was completed by 25 radiography directors (89% response rate). Sixteen percent of respondents, all metropolitan‐based, indicated a RADS was in operation ( n = 4/25; 16%). Respondents without a RADS ( n = 21/21; 100%) expressed interest in a trial. Just over half ( n = 13/25; 52%) of the respondents believed their staff members were not trained appropriately to implement a RADS successfully. Conclusion: This study found an infrequent use of RADSs in Queensland public hospitals. This finding presents a unique opportunity for medical imaging professionals to enhance communication between the facets of a multidisciplinary emergency team via the implementation of RADS complemented by a radiographer commenting system. Abstract : This investigation sought to ascertain the use of radiographer abnormality detection systems within Queensland public hospitals. The results showed an infrequent use of such a system.